Kemampuan Pemecahan Masalah Matematis Peserta Didik yang Diajar Dengan Model Pembelajaran Missouri Mathematics Project (MMP) Disertai Strategi Think-Talk-Write (TTW) di SMP Negeri 2 Lengayang Pesisir Selatan - Susanto, Andi; Syaveta, Rara Anggun (Math Educa Journal, 2018)
This research is driven by the low level of problem solving ability of 8th grade students of SMPN 2 Lengayang. This study aims to determine the problem-solving ability of mathematics students taught by matrix Missouri mathematics project with a strategy of Think-Talk-Write better than students who use the scientific approach. This research is a quasy experiment research. The population of this research is all students of class VIII SMPN 2 Lengayang, and sampel is this research class VIII.A and class VIII.E. Based on the results of this study obtained the average value of mathematical problem-solving skills of learners who were taught by MMP method with TTW strategy is 76 and the usual learning is 68. After hypothesis testing using t-test, known ttable = 1,64 and tcount = 2,23 with 95% confidence level, this means that this indicates that the accepted hypothesis means the ability to solve mathematical problems of students with MMP with scientific approach.Keyword : Mathematical Problem Solving Skills, Learning Model Type Missouri mathematics project (MMP), and strategy of Think-Talk-Write (TTW)